1997
DOI: 10.1053/jhep.1997.v25.pm0009021954
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a swelling-activated anion conductance in homozygous typing cell hepatoma cells

Abstract: in volume includes the opening of ion efflux pathways to Liver cell volume and intracellular ion concentrations decrease the amount of intracellular ions. 6 Solute efflux leads are maintained within a narrow physiologic range by to recovery toward basal values, a process referred to as reguregulated changes in membrane ion permeability. These latory volume decrease (RVD). [9][10][11][12] The ability to recover from studies of homozygous HTC hepatoma cells, a model cell swelling is a general property of mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 8 publications
2
34
0
Order By: Relevance
“…Extracellular ATP causes rapid increase of the intracellular Ca 2 þ concentration and subsequent activation of membrane Cl À channels through purinergic receptors in the process of bile formation by cholangiocytes. [54][55][56][57] In the present study, we demonstrated the decrease of AE activity by the extracellular ATP and partial recovery of the AE activity by the induction of ANXA2. The phosphorylation status of the amino-acid residue of ANXA2 also modulates its binding affinity to the membrane.…”
Section: Discussionsupporting
confidence: 66%
“…Extracellular ATP causes rapid increase of the intracellular Ca 2 þ concentration and subsequent activation of membrane Cl À channels through purinergic receptors in the process of bile formation by cholangiocytes. [54][55][56][57] In the present study, we demonstrated the decrease of AE activity by the extracellular ATP and partial recovery of the AE activity by the induction of ANXA2. The phosphorylation status of the amino-acid residue of ANXA2 also modulates its binding affinity to the membrane.…”
Section: Discussionsupporting
confidence: 66%
“…Volume recovery is dependent on channel-mediated Cl Ϫ efflux. 13,15 Addition of chelerythrine (25 µmol/L) to hypotonic buffer did not affect the magnitude of swelling, but completely prevented volume recovery in both cell types (Table 1, Fig. 6).…”
Section: Figmentioning
confidence: 93%
“…Increases in HTC cell volume stimulated by uptake of alanine (29) or exposure to hypotonic buffer (30,31) are followed by ATP efflux, receptor activation, and opening of membrane Cl Ϫ channels (30,33). Cells were passaged at weekly intervals and maintained in HCO 3 Ϫ -containing minimal essential medium (Life Technologies, Inc.) supplemented with 10% heat-inactivated fetal bovine serum, L-glutamine (2 mM), penicillin (100 IU/ml), and streptomycin (100 g/ml) as described previously (34).…”
Section: Methodsmentioning
confidence: 99%